Enhancing the Demands of ZAMPEN-SUCs AFNR Graduates Through Curriculum Intervention Using Modular Approach with High S and T Content - Sarmiento, Chona Q.; Saavedra, Paterna J. (JPAIR Multidisciplinary Research, 2018)
The contribution of the DOST-PCARRD AFNR Project 2.3 from SY 2009-2011 has demonstrated transformed changes in the AFNR curriculum. These changes are well recognized as it has attracted more enrollees in the region’s dwindling AFNR courses. The study presented the implementation of the AFNR Project 2.3 in Zamboanga Peninsula as an intervention to the observed down trend enrolment in the AFNR courses since SY 2001 onwards. The AFNR Project 2.3 was implemented for the duration of two years from SY Feb 2009-Feb 2011. The project at the regional level enabled students’ preparation for employability, equipped them with entrepreneurial skills, with the integration of strong S & T contents in the courses through the modular approach. The Western Mindanao State University (WMSU) played the lead institution in the region with three collaborating SUCs, namely, JH Cerilles State College (JHCSC), Zamboanga State College of Marine Sciences and Technology (ZSCMST), and the two campuses of Jose Rizal Memorial State University (JRMSU). Towards the end of its implementation for the second year, the project achieved the following gains based on its objectives: (a) Enriched 10 BS curricular programs (b) reviewed 81 AFNR subjects (c)enriched at least 70 courses in the 10 BS AFNR Programs and (d) introduced 30 short term courses respectively.